Prática de linguagem e a constituição identitária num espaço hospitalar multilíngue e intercultural - Alencar, Sílvia Helena Freitas (2012)
The research is an analysis of the language and identity from the narratives of three women from different cultural and linguistic profile: two Brazilian (one indigenous and one non-indigenous) and a Guyanese (non-indigenous) who lived in the period from April to June 2009, an experience of contact in a multilingual public hospital space. The aim was to investigate the language practices and identity formation of individuals who lived in a room of Maternal and Child Hospital, in Boa Vista, Roraima state capital. It is an approach based in Applied Linguistics as an area of knowledge in dialogue with other knowledge such as Anthropology, Social Sciences, Cultural Studies, among others, thus outlining an interdisciplinary character. In this perspective, the narratives of these women, recorded in a field diary and semistructured audio taped interviews were scripted and triangulated with other records, such as interviews with management and employees of the hospital, official documents provided by the institution, photos and sketches. For the analysis, I bring an initial discussion of language and identity constructs, passing by others, such as representation, culture, memory, orality, narrative, otherness, and the central axis of the language. The research question that guided the study was: How did language practices and identity process happen in a multilingual and intercultural hospital space? The discussions developed from this question show that contact with different language and culture practices provided women the redefinition of themselves and others and shows as expectation that this work visible the existence of a complex sociolinguistic hospital context. I noticed also that the established practices in place revealed the possibility of expanding the institutional actions that encompass the heterogeneity and the opening of an intercultural dialogue.